Sustainable design approaches towards green higher education campus - Delgado, M. J.; Almeida, I. D. de.; Montagna, G. (Human Dynamics and Design for the Development of Contemporary Societies (AHFE 2022), 2022)
The primary goal of our work is to address the issues concerning the application of sustainability concepts in the Higher Education Campus of the Faculty of Architecture at Universidade de Lisboa. Sustainable actions and attitudes are part of the sustainable principles of the Sustainable Development Goals adopted in the 2030 Agenda by all United Nations member states. This exploratory research is based on a review of the international literature specialising in sustainability assessment in Higher Education Institutions. A qualitative research approach was applied, using a questionnaire adapted from the European University Association in 2021, as a research instrument to know the perception and opinion of the Faculty of Architecture (FA) academic community on some of the collective actions of greening. A qualitative interpretation and discussion of the obtained data were performed based on a survey conducted on a non-probabilistic sample selected from Campus users. With this investigation, we intend to know the challenges and initiatives practised on this Campus in defence of sustainability and contribute towards a changeover in the environmental, social, and economic awareness of the campus community.